Taxes and Entrepreneurship: Impact on New Business Creation - Pratama, Hadi (Golden Ratio of Taxation Studies, 2023)
This study investigates the intricate relationship between tax policies and entrepreneurship, aiming to provide comprehensive insights into how taxes influence entrepreneurial behavior and outcomes. Adopting a qualitative approach, the research synthesizes existing literature on taxes and entrepreneurship, drawing on a diverse range of scholarly articles, books, and reports. The research methodology involves systematic literature search, data extraction, thematic analysis, and critical appraisal of findings. The study finds that tax rates significantly impact entrepreneurial activity, with higher tax rates generally associated with lower rates of new business creation. Moreover, complex tax systems and compliance costs pose barriers to entry for aspiring entrepreneurs, diverting resources away from productive activities. However, the impact of taxes on entrepreneurship extends beyond mere rate considerations, encompassing factors such as tax incentives, institutional frameworks, and socio-economic conditions. Tax policies that offer targeted incentives for startup investment, research and development (R&D), and small business development can mitigate the negative effects of high tax rates and promote entrepreneurial activity. Furthermore, favorable business climates, streamlined regulatory processes, and transparent tax administration contribute to an enabling environment for startups to thrive and innovate. The study highlights the need for policymakers to adopt a holistic approach to tax policy design that balances revenue objectives with entrepreneurship promotion.